2021
DOI: 10.3390/antiox10111712
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nrf2 in Skeletal Muscle on Exercise Capacity

Abstract: Nuclear factor erythroid 2-related factor 2 Nfe2l2 (Nrf2) is believed to play a crucial role in protecting cells against oxidative stress. In addition to its primary function of maintaining redox homeostasis, there is emerging evidence that Nrf2 is also involved in energy metabolism. In this review, we briefly discuss the role of Nrf2 in skeletal muscle metabolism from the perspective of exercise physiology. This article is part of a special issue “Mitochondrial Function, Reactive Oxygen/Nitrogen Species and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…However, under stress conditions, NFE2L2 translocates into the nucleus and binds to antioxidant response elements of the target cytoprotective genes. Studies using NFE2L2-deficient mice on a C57BL/6 background demonstrated that NFE2L2 is important for antioxidant enzymes in skeletal muscles [43]. Thus, we speculate that a similar role for this transcription regulator exists in the skeletal muscle of dairy cows.…”
Section: Antioxidant Responsementioning
confidence: 71%
“…However, under stress conditions, NFE2L2 translocates into the nucleus and binds to antioxidant response elements of the target cytoprotective genes. Studies using NFE2L2-deficient mice on a C57BL/6 background demonstrated that NFE2L2 is important for antioxidant enzymes in skeletal muscles [43]. Thus, we speculate that a similar role for this transcription regulator exists in the skeletal muscle of dairy cows.…”
Section: Antioxidant Responsementioning
confidence: 71%
“…NFκB activity can be increased by ROSP but also by several other stimuli such as free fatty acids (FFA), advanced glycation products, and inflammatory cytokines induced by oxidative stress [ 19 ]. On the other way, high levels of ROSP activate the nuclear factor, erythroid 2-like 2 (Nrf2) pathway leading to increased transcription of genes coding for antioxidant proteins, and consequently inducing the antioxidant ROSP-fighting effects [ 76 ].…”
Section: Oxidative Stress and Inflammation: Two Essential Harmsmentioning
confidence: 99%
“…In this fashion, Nrf2 is closely tied to muscular endurance against ROS and other associated oxidative byproducts of myocyte mitochondrial respiration. Within skeletal muscle itself, Nrf2 is part of the antioxidant response to ROS generated by aerobic respiration within striated myocytes and helps to reduce citrate synthase and COX-mediated inflammation [ 101 ]. In cases of exercise, muscle contractions (100 and 50 Hz) and long periods of aerobic exertion have been found to stimulate Nrf2 response [ 101 ].…”
Section: Clinical Nrf2 Modulatorsmentioning
confidence: 99%
“…Within skeletal muscle itself, Nrf2 is part of the antioxidant response to ROS generated by aerobic respiration within striated myocytes and helps to reduce citrate synthase and COX-mediated inflammation [ 101 ]. In cases of exercise, muscle contractions (100 and 50 Hz) and long periods of aerobic exertion have been found to stimulate Nrf2 response [ 101 ]. So why does exercise-mediated Nrf2 elevation prevent cardiomyopathy instead of possibly promoting it as seen with exogenous compounds?…”
Section: Clinical Nrf2 Modulatorsmentioning
confidence: 99%